Erzincan Tulum Cheese - Ayla Arslaner; Özgenur Türkmen (Turkish Journal of Agriculture: Food Science and Technology)
Erzincan Tulum cheese with its characteristic taste and aroma is one of the most preferred traditional cheese varieties are those from Turkey. Physical, chemical and microbiological changes that occur during ripening give the cheese characteristics. The characteristics of the Erzincan Tulum cheese are closely related to the geography in where it is produced and the human factors affecting each stage of the production method. However, the lack of a standard in production has prevented Erzincan Tulum cheese from achieving the economic value it deserves and could not provide sufficient contribution to the socio-economic development of the region. The most important reasons for this are the inadequacy of legislation and supervision, the lack of awareness of the Geographical Indication (GI) registration in the producer, and the fact that the institutions and organizations that register have not used GIs effectively, besides the technological reasons such as variety, quantity and microbiological quality of rennet used in cheese production, variability in milk quality, ripening conditions and durations vary, and the absence of a standard packaging material. In this review, the findings obtained from the researches related to technology, legislation, marketing and registration of Erzincan Tulum cheese which has a significant potential in terms of contribution to the economy of the region and country in which it is produced, are evaluated.